Dynamic Spin Labeling Angiography in Extracranial Carotid Artery Stenosis - Warmuth, Carsten; Rüping, Maria; Förschler, Annette; Koennecke, Hans-Christian; Valdueza, Jose Manuel; Kauert, Andreas; Schreiber, Stephan J.; Siekmann, Ralf; Zimmer, Claus (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Similar to digital subtraction angiography, dynamic spin labeling angiography (DSLA) provides time-resolved measurements of the influx of blood into the cerebral vascular tree. We determined whether DSLA may help in assessing the degree of stenosis and whether it provides information about intracerebral collateralization and allows us to monitor the hemodynamic effects of vascular interventions.METHODS: We developed a segmented DSLA sequence that allowed the formation of images representing inflow delays in 41-ms increments. Thirty patients with unilateral carotid artery stenosis and 10 control subjects underwent DSLA. Arrival times of the labeled arterial blood bolus were measured in the carotid siphon (CS) and the middle cerebral artery (MCA) on both sides, and the corresponding side-to-side arrival time differences (ATDs) were calculated. ATDs before and after carotid endarterectomy or percutaneous angioplasty were studied in 10 patients.RESULTS: The degree of stenosis was significantly correlated with ATD in the cerebral vessels. Receiver operating characteristic analysis yielded a cutoff CS ATD of 110 ms to separate stenoses <70% from those ≥70%, with a sensitivity of 90% and a specificity of 67%. In one third of patients, ATD was higher in the MCA than in the CS; this finding suggested an absence of collateralization. Most patients had reduced ATD in the MCA. The degree of ATD reduction was regarded as a quantitative measure of collateralization. Successful intervention resulted in normalized ATDs.CONCLUSION: DSLA is a promising method that allowed us to noninvasively quantify the hemodynamic effect of extracranial carotid stenosis and the resulting intracranial collateralization.